Earthworm inspired lubricant self-pumping hydrogel with sustained lubricity at high loading - Shuanhong Ma; Lunkun Liu; Weiyi Zhao; Renjie Li; Xiaoduo Zhao; Yunlei Zhang; Bo Yu; Ying Liu; Feng Zhou (Nature Communications)
Abstract The development of mechanically robust super-lubrication hydrogel materials with sustained lubricity at high contact pressures is challenging. In this work, inspired by the durable lubricity feature of the earthworm epidermis, a multilevel structural super-lubrication hydrogel (MS-SLH) system, the so-called lubricant self-pumping hydrogel, is developed. The MS-SLH system is manufactured by chemically dissociating a double network hydrogel to generate robust and wrinkled lubrication layer, and then laser etching was used to generate cylindrical texture pores as gland-like pockets for storing lubricants. The surface of MS-SLH system shows ultrafast hydration characteristics and reversible pore-closing and pore-opening behavior. The current MS-SLH system shows excellent SL features, as follows: a very low COF (~0.0079) at high contact pressure condition (P: 11.32 MPa); a stable and robust SL lifespan (COF: ~0.0028, P: 8.48 MPa, 100k cylces) without surface wear; and a sustained lubricity period (3700 cycles) with limited lubricant volume (5 μL) in air. The robust and sustained lubricity of the MS-SLH system is likely attributed to the synergy from the strong electrostatic repulsion effect at the sliding interface, the robust but compliant modulus of the dissociation lubrication layer, and the self-pumping lubricant release from the gland-like pocket of the texture pores during the dynamic shearing process. The demonstration experiments based on self-built equipments intuitively exhibit durable SL behavior of MS-SLH system. This work provides an easy strategy for the large-scale manufacture of high-performance water-lubrication coatings suitable for high-end medical devices or moving parts.